2018
DOI: 10.1016/j.ijscr.2018.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Bowel perforation by lumbar-peritoneal (LP) shunt: A rare complication of neurosurgery

Abstract: HighlightsLumbar-peritoneal (LP) and ventriculo-peritoneal (VP) shunt placement is the treatment of choice for diversion of cerebrospinal fluid (CSF) from the subarachnoid space into the peritoneal cavity.Perforation of the bowel by lumbar-peritoneal or ventriculo-peritoneal shunt is an extremely rare complication.We report a case of a 72 old female patient with LP shunt for raised intracranial pressure, who presented with LP shunt catheter protruding from anus.She was surgically treated with removal of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Abdominal complications account for 10–30% including various types such as occlusive/mechanical (15%), infections (5%), cyst formation (1–2%), and visceral perforation (0.2–0.3%) [ 1 , 2 ]. The catheter can migrate into the intestine, stomach, bladder, vagina, scrotum, penis, navel [ 3 , 4 , [5] , [6] , [7] , [8] , [9] , [10] , [12] , [13] , [14] ]. Intestinal perforations are very rare: 0.01–0.07% of abdominal complications [ 2 , 12 , 18 ], and mortality due to these complications can be up to 15% (mostly due to infection) [ 2 , 3 ].…”
Section: Clinical Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal complications account for 10–30% including various types such as occlusive/mechanical (15%), infections (5%), cyst formation (1–2%), and visceral perforation (0.2–0.3%) [ 1 , 2 ]. The catheter can migrate into the intestine, stomach, bladder, vagina, scrotum, penis, navel [ 3 , 4 , [5] , [6] , [7] , [8] , [9] , [10] , [12] , [13] , [14] ]. Intestinal perforations are very rare: 0.01–0.07% of abdominal complications [ 2 , 12 , 18 ], and mortality due to these complications can be up to 15% (mostly due to infection) [ 2 , 3 ].…”
Section: Clinical Discussionmentioning
confidence: 99%
“…However, some authors believe that this complication is often observed in young children due to a thin, easily punctured intestinal wall [ 6 ]. Most cases of a catheter that entering into the intestine are diagnosed when the tube was found outside of the anus [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , 13 , [15] , [16] , [17] , [18] , [19] ] or the mouth [ 14 , 15 ], or comes out of the penis and navel [ 15 , 17 ]. In cases where the tube does not come out (anus, mouth, penis, vagina, etc.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Peritonitis, intraperitoneal abscess, and sepsis should always be treated with exploratory laparotomy, lavage, primary bowel-wall closure, and shunt removal [4,8]. The ventricular part should be drained for at least 14 days, with antibiotic treatment as prophylaxis [4,10]. Once CSF cultures are repeatedly negative, a new peritoneal shunt catheter can be placed at the opposite site [10].…”
Section: Discussionmentioning
confidence: 99%
“…The ventricular part should be drained for at least 14 days, with antibiotic treatment as prophylaxis [4,10]. Once CSF cultures are repeatedly negative, a new peritoneal shunt catheter can be placed at the opposite site [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation